A perspective on how ATM lost control. - Crosby, Simon
Contrary to the initial high expectations, ATM failed to become the universal network technology covering all services and running from the desktop to the backbone. This paper tries to identify the technological problems that contributed to this failure.
Keywords: Computer systems organization; Computer communication networks; Network architecture and design; Asynchronous Transfer Mode (ATM).; Internetworking; Standards (e.g., TCP/IP).; Computing milieux; History of computing; Systems